2019
DOI: 10.1017/s0007114518003215
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing the efficacy of micellised and fat-soluble vitamin D3 supplementation in healthy adults

Abstract: Nanoemulsion formulation of vitamin D3 have been shown to have better bioavailability than the coarse emulsion preparation in vitro and in vivo animal studies. In the absence of randomised trial in humans, comparing the efficacy of nanotechnology-based miscellised vitamin D3 over conventional vitamin D3, we undertook this study. A total of 180 healthy adults were randomised to receive either micellised (DePura, group A) or conventional vitamin D3 (Calcirol, group B) at a monthly dose of 60 000 IU (1500μg) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…VD sufficiency achieved in 90% subjects with monthly dose of 60,000 IU is more or less similar (95%) to that achieved with oral dose of 2000 IU/day, though with a higher increase in serum 25(OH)D concentration in group C. This finding is supported by reports from Niet et al in adults 29 and Marwaha et al 37 among others 31,[38][39][40] who documented 100% and 90% subjects attaining serum 25(OH)D concentration >20 ng/ml respectively with 60,000 IU and 50,000 IU oral monthly doses. These results assume significance in view of the fact that once monthly cholecalciferol supplementation may be convenient for people and ensure better compliance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…VD sufficiency achieved in 90% subjects with monthly dose of 60,000 IU is more or less similar (95%) to that achieved with oral dose of 2000 IU/day, though with a higher increase in serum 25(OH)D concentration in group C. This finding is supported by reports from Niet et al in adults 29 and Marwaha et al 37 among others 31,[38][39][40] who documented 100% and 90% subjects attaining serum 25(OH)D concentration >20 ng/ml respectively with 60,000 IU and 50,000 IU oral monthly doses. These results assume significance in view of the fact that once monthly cholecalciferol supplementation may be convenient for people and ensure better compliance.…”
Section: Discussionsupporting
confidence: 82%
“…In India, there is a lack of clear-cut data on the optimal dose/schedule of VD supplementation to achieve serum 25(OH)D >20 ng/ml, owing to heterogeneity of the studies about age, duration (8 weeks to 1 year), doses (200 to 60,000 IU), sample size, level of serum 25(OH)D considered sufficient and populations studied [13][14][15][16] . Hence, we undertook this randomized study with to evaluate the comparative effectiveness of three different daily dosage regimens of oral cholecalciferol supplementation among themselves and with once-monthly schedule.…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability of nutrients that have poor water solubility can be increased by nanotechnology (11,20). Evidence showed that nanoparticles of vitamin D 3 might also enhance important properties of vitamin D supplements, like therapeutic efficacy, photo-stability, and biodegradation (21). Moreover, in our previous study, we have compared the bioequivalence of vitamin D 3 oral solution with that of conventional vitamin D 3 tablets and capsules.…”
Section: Resultsmentioning
confidence: 99%
“…Other in-vitro research shows potential to improve absorption by incorporating fat soluble vitamins within a micelle before consumption (Goncalves et al 2013). Building on this in-vitro work, Marwaha and colleagues report greater increases in 25(OH)D with a water micellised vitamin D supplement compared to a conventional vitamin D supplement in children and adults (Marwaha et al 2016(Marwaha et al , 2019. Similarly.…”
Section: Introductionmentioning
confidence: 99%